Altered cardiovascular rhythmicity in children with white coat and ambulatory hypertension - Litwin, Mieczysław; Simonetti, Giacomo D.; Niemirska, Anna; Ruzicka, Marcel; Wühl, Elke; Schaefer, Franz; Feber, Janusz (Pediatric research, 2010)
Adults with ambulatory hypertension or white coat hypertension (WCH) display abnormal cardiovascular rhythms. We studied cardiovascular rhythms by Fourier analysis of 24-h ambulatory blood pressure (BP) measurement profiles in 129 hypertensive children, 54 children with WCH, and 146 age-, height-, and gender-matched healthy subjects.
Gesehen am 28.03.2023